MgAl Layered Double Hydroxides Intercalated with EDTA: Cu(II) Recovery and Mechanism. Issue 36 (23rd September 2020) - Chen, Liangzhe; Tu, Qian; Yang, Xingyan; Hu, Xiaolin; Sun, Xinyu; Li, Houbin
Abstract: In water treatment, it is a valid way to remove Cu(II) efficiently via layered double hydroxides (LDHs) intercalated with chelate, but the desorption and its mechanism remain an unsolved difficult problem. To solve this problem, MgAl LDHs intercalated with EDTA (MgAl‐EDTA‐LDHs) was synthesized by one‐step co‐precipitation method, and applied to recover Cu 2+ . The characterizations of SEM, XRD, XPS, EA and AAS were employed, and the results showed that MgAl‐EDTA‐LDHs exhibited a typical lamellar structure, the adsorption capacity of MgAl‐EDTA‐LDHs on Cu 2+ could reach 79.69 mg/g, which was attributed to the chelation of EDTA and chemical bonding of hydroxyl (−OH) on the surface of LDHs layers. In addition, the adsorption capacity could achieve 45.75 mg/g after eluting by Na2 CO3 solution, which was relevant to the ion exchange by CO3 2− . Herein, the adsorption and desorption mechanism of MgAl‐EDTA‐LDHs on Cu 2+ was expounded, which may pave a new way to recover the heavy metal and provide a theoretical guidance for future research. Abstract : Mg 2+, Al 3+ and EDTA 4− were employed as raw materials, MgAl‐EDTA‐LDHs was prepared with a pH of 9 via co‐precipitation method. Then, Cu(NO3 )2 ⋅ 3H2 O served as adsorbate, was adsorbed by MgAl‐EDTA‐LDHs in a short time. Next, the obtained MgAl‐(Cu‐EDTA)‐LDHs was desorbed by Na2 CO3 solution and Cu 2+ was acquired in solution. The adsorption mechanism is attributed to the chelation of EDTA, accompanied by the chemical bonding of −OH on the surface of layer, and the recovery mechanism could be explained by ion exchange with CO3 2− .